Extract and Active Principal of the Neotropical Vine Souroubea sympetala Gilg. Block Fear Memory Reconsolidation - Murkar, Anthony; Cayer, Christian; James, Jon; Durst, Tony; Arnason, John T.; Sanchez-Vindas, Pablos E.; Otarola Rojas, M.; Merali, Zul (Frontiers in Pharmacology, 2019)
Background: Souroubea sympetala Gilg.is a neotropical vine native to Central America, investigated as part of a targeted study of the plant family Marcgraviaceae. Our previous research showed that extract of S. sympetala leaf and small branch extract had anxiolytic effects in animals and acts as an agonist for the GABAA receptor at the Benzodiazepine binding site. To date, the potential effects of S. sympetala and its constituents on reconsolidation have not been assessed. Reconsolidation, the process by which formed memories are rendered labile and susceptible to change, may offer a window of opportunity for pharmacological manipulation of learned fear. Here, we assessed the effects of S. sympetala crude extract and isolated phytochemicals (orally administered) on the reconsolidation of conditioned fear. In addition, we explored whether Betulin (BE), a closely related molecule to betulinic acid (BA, an active principle component of S. sympetala) has effects on reconsolidation of learned-fear and whether BE may synergize with BA to enhance attenuation of learned-fear. Method: Male Sprague-Dawley rats received six 1.0 mA continuous foot-shocks (contextual training). 24h later, rats were re-exposed to the context (but in the absence of foot-shocks). Immediately following memory retrieval (recall) rats received oral administration of S. sympetala extract at various doses (8-75 mg/kg) or Diazepam (1 mg/kg). In separate experiments we compared the effects of BA (2 mg/kg), BE (2 mg/kg), and BA + BE (2 mg/kg BA + 2 mg/kg BE). The freezing response was assessed either 24 h later (day 3) or 5 d later (day 7). Effects of phytochemicals on fear-expression were also explored using the elevated plus maze paradigm. Results: S. sympetala leaf extract significantly attenuated the reconsolidation of contextual fear at the 25 mg/kg and 75 mg/kg doses but not at the 8 mg/kg dose. Furthermore, BA + BE, but not BA or BE alone, attenuated the reconsolidation of learned fear and exerted an anxiolytic-like effect on fear expression.